Understanding Tesla Motors’ performance through the lens of transaction cost economics and resource-based view theories - Voillemot, Adrien (2016)
Transaction cost economics and the resource-based view are two influential schools of thought explaining vertical integration. The former argues that a firm is likely to contract with another one when the costs of transaction are lower than the internal costs of coordination of the firm. The latter accounts for vertical integration by the ownership of superior resources and capabilities. Researchers recently called for using both theories together to break down make-or-buy decisions, highlighting their similarities. Tesla Motors, an electric car maker, differs from other established car manufacturers by its high level of vertical integration. This study aims at explaining the company’s contrasting performance by examining its vertical integration strategy through the lens of these two theories. Results indicate that both theories have complementarity aspects and can be used within a single analytical framework, although further clarifications are required in some instances. Implications for future research as well as recommendations for managers conclude this work.